Characterization of the human multidrug resistance protein isoform MRP3 localized to the basolateral hepatocyte membrane - König, Jörg; Rost, Daniel; Keppler, Dietrich (Hepatology, 2003)
Several members of the multidrug resistance protein (MRP) family are expressed in the liver. Adenosine triphosphate (ATP)-dependent transport of glutathione and glucuronoside conjugates across the hepatocyte canalicular membrane is mediated by the apical MRP isoform, MRP2 (APMRP), also known as canalicular multispecific organic anion transporter (cMOAT). We have cloned an additional MRP isoform, MRP3, from human liver and localized it to the basolateral membrane domain of hepatocytes. Basolateral MRP (BLMRP) is composed of 1,527 amino acids and encoded by 4,581 base pairs of complementary DNA. Northern blotting of various human tissues indicated an expression of MRP3 in the liver, colon, pancreas, and, at a lower level, in the kidney. The amino acid identity of MRP3 with MRP1 and MRP2 is 58% and 48%, respectively. These three isoforms, encoded by genes on different chromosomes, have a similar predicted topology of transmembrane segments and ATP-binding domains. Antibodies raised against two peptide sequences of MRP3 that are not shared by other MRP family members detected recombinant MRP3 expressed in polarized MDCK cells. Both antibodies served to localize MRP3 to the basolateral membrane of hepatocytes. Double-label immunofluorescence microscopy confirmed that MRP3 was not detectable in the canalicular membrane domain. A particularly strong expression of the MRP3 protein was observed in the basolateral hepatocyte membrane of two patients with Dubin-Johnson syndrome who are deficient in MRP2. These results indicate that the basolateral MRP isoform, MRP3, may be upregulated when the canalicular secretion of anionic conjugates by MRP2 is impaired
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 23.02.2021